RECYCLING BEHAVIOUR AMONG MALAYSIAN TERTIARY STUDENTS (Journal of Technology and Operations Management, 2016)
Tertiary institutions are considered as â€œsmall citiesâ€ and the enculturation of sustainable practices are vital due to its size and the impact that campus activities have on the environment and society. The sustainable practices such as recycling and reduction of carbon footprint are one of the examples that may lead to greening the tertiary institution and sustainable quest for UI Green Metric achievement. The tertiary campus is seen as offering an ideal setting for exploring and practicing sustainability. This study explored the current recycling behaviour in a tertiary setting; using a survey design to address the research questions and objectives. Study found that the tertiary students are prone to recycling due to the situational factors which are convenience and incentive as well as personal factors which included knowledge and social norm. Study concluded that in achieving the UI Green Metric, tertiary institutions should offer a convenience setting that indirectly enculturates the sustainable practices among the campus community.